Between Webs and Posters: Science Communication and Spiders (Arachnida: Araneae) in the Leonelo Oviedo Ecological Reserve, San José, Costa Rica (Biocenosis, 2025)
Urban vegetation patches support wildlife conservation; however, they also present a number of challenges. One of the most significant issues is the interaction between wildlife and humans, as it can lead to conflicts and directly affect both parties. The Leonelo Oviedo Ecological Reserve (RELO) is an urban forest patch located on the Rodrigo Facio University Campus of the University of Costa Rica, in San José. It is the habitat of many spider species, some of which have direct interactions with people who use the area and its surroundings. These interactions can be detrimental to the spiders due to various social factors, including the widespread human rejection of these arthropods. To mitigate this issue, a science communication initiative was proposed using infographics placed throughout the Leonelo Oviedo Ecological Reserve. These infographics provided relevant information about the biology, natural history, and behavior of several spider species, selected with the support of an expert and the Protected Areas Network of the University of Costa Rica (RAP). The initiative intended to promote neutral or positive attitudes toward the spiders inhabiting this space. The results showed favorable opinions toward both the spiders and the infographics, highlighting the appeal of their content and design. Therefore, this underscores the importance of implementing conservation efforts that include public science communication.
Keywords: arachnids; Rodrigo Facio University Campus; biological outreach; infographics; labeling